(untitled) (Journal of Philosophy Culture and Political Science, 2021)
In black Africa, apart from the abundance of its natural resources and the more or less untouched side of its nature or, if you will, what is still left of it, the picture that we make of it is that of underdevelopment – in opposition to the development that characterizes the countries of the North – as well as its procession of generalized ills (violences, wars, famines, epidemics, etc.), which seems to have become consubstantial – as they are taken up in unity by social scientists and interested in it only by developers and other NGOs. It can be noted that this canvas, which seems to be dedicated to reporting on the deep nature of the continent, necessarily includes within it the “indispensable building blocks” of its definition. Indeed, the identification of violences, for example armed conflicts such as civil wars, rebellions, insurrections, but also forms of nepotism-type violences that distinguish more than elsewhere on the continent, the Central African region, as well as the phenomena of corruption, clientelism, and other financial gabegies, are all characteristic elements of black Africa today. Anything that seems excessively paradoxical insofar as, this Africa singularly, that of the center in particular is full in its soil and basement of immense natural resources that are the subject of uninterrupted exploitation from the very advent of the colonial encounter. Resources that, if they were being exploited by Western "partners" on the one hand, and, if the revenues generated by this exploitation were equitably redistributed to the population in the form mainly of basic services (health, education, housing and essential infrastructure, roads and bridges, port and airports in particular), on the other hand would effortlessly compensate for these "evils" which are, it is seen, more the consequence of too much wealth of these regions articulated in the principle of capitalism , unfortunately for them, the leitmotif is first and foremost a profit described as immoral at the expense of human reason. Key words: Africa, decolonization, violence, law, philosophy of history, philosophical anthropology, political instability.